Understanding and using the Naglieri general ability tests : a call for equity in gifted education - Brulles, Dina; Lansdowne, Kimberly; Naglieri, Jack A. (Free Spirit Publishing, an imprint of Teacher Created Materials, Inc., 2022)
"Designed for use with the Naglieri General Ability Tests, this book will help educators, administrators, and school psychologists support students who take the tests. Explains the need for the tests, how to use them to identify gifted students, and how to use them to make gifted education more equitable"--